Scaling measurement of oil production wastewater as a comprehensive environmental engineering experiment. Issue 3 (May 2021) - Yu, Tao; Zhang, Xiaofei; Yang, Bo; Jinling, Li; Chen, Gang; Qu, Chengtun
Abstract: In the process of scaling the measurement of oil production wastewater using the bottle test method, the deposition and attachment of scaling crystals on the bottle wall lead to a small measurement result and a large error compared to the actual measurement. The scaling amount of oil production wastewater is measured by adding quantitative clay and inducing adsorption, gathering, and deposition of scaling crystals onto the surface of clay particles. Comparing with the theoretical value, the determination result is more accurate than the result of the bottle test method. The comprehensive experimental design described in this paper applies various topics of colloid and interface chemistry, such as scale crystal growth, clay diffusion double electric layer, and micelle structure. We believe that this design will help students majoring in environmental engineering to master the measurement method of scaling the amount of oil production wastewater and strengthen their ability to solve practical problems.